Joss Whedon as Shakespearean moralist narrative ethics of the Bard and the Buffyverse - Rabb, J. Douglas 1942-; Richardson, J. Michael 1951- (McFarland, 2015)
"This study in narrative ethics contends that Whedon is the Shakespeare of our time arguing that Whedon's work is more in harmony with the early modern values of Shakespeare than with modern ethics Included is a detailed discussion of representative works of Shakespeare and Whedon, showing how they can and should be read as forms of narrative ethics"..